Cardiac toxicity of lung cancer radiotherapy - Vojtíšek, Radovan (Reports of practical oncology and radiotherapy, 2020)
Radical radiotherapy of lung cancer with dose escalation has been associated with increased tumor control. However, these attempts to continually improve local control through dose escalation, have met mixed results culminating in the findings of the RTOG trial 0617, where the heart dose was associated with a worse overall survival, indicating a significant contribution to radiation-induced cardiac morbidity. It is, therefore, very likely that poorly understood cardiac toxicity may have offset any potential improvement in overall survival derived from dose escalation and may be an obstacle that limits disease control and survival of patients. The manifestations of cardiac toxicity are relatively common after high dose radiotherapy of advanced lung cancers and are independently associated with both heart dose and baseline cardiac risk. Toxicity following the treatment may occur earlier than previously thought and, therefore, heart doses should be minimized. In patients with lung cancer, who not only receive substantial heart dose, but are also older with more comorbidities, all cardiac events have the potential to be clinically significant and life-threatening. Sophisticated radiation treatment planning techniques, charged particle therapy, and modern imaging methods in radiotherapy planning, may lead to reduction of the heart dose, which could potentially improve the clinical outcomes in patients with lung cancer. Efforts should be made to minimize heart radiation exposure whenever possible even at doses lower than those generally recommended. Heart doses should be limited as much as possible. A heart dosimetry as a whole is important for patient outcomes, rather than emphasizing just one parameter.
Keywords: Heart dose constraints; Cardiac toxicity; Lung cancer; Thoracic radiotherapy